Alteração de Cor e Sorção de Resinas Compostas Imersas em Água e Soluções Corantes - LAIBER, L. P. (2018)
Made available in DSpace on 2018-08-01T23:25:59Z (GMT). No. of bitstreams: 1 tese_10510_Dissertação Lara.pdf: 16818868 bytes, checksum: 37c0a6bac2b160563378a75d08789a3f (MD5) Previous issue date: 2016-12-15